PENGARUH WAKTU PEMANGKASAN PUCUK TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Mahargian Hammam Mu'afa; Djarwatiningsih Djarwatiningsih; Didik Utomo Pribadi (UPN VETERAN JAWA TIMUR, 2020)
Increasing production of cayenne plant commodities can be done easily and cheaply, enough to do with the selection of varieties and appropriate cultivation techniques, one of which is the time of pruning. The purpose of this study was to determine the growth and yield of three varieties of cayenne pepper due to the time of shoot pruning. This research was conducted in the UPT greenhouse for Food Crops and Horticulture Agribusiness Development East Java, Sidoarjo in February-June 2019. This research was a factorial experiment prepared using a Completely Randomized Design (CRD) consisting of two factors and repeated three times. The first factor is the time of shoot topping with four levels of treatment, including without topping, topping 7 HST, 14 HST and 21 HST. The second factor is variety with three levels, namely, Mhanu F1 variety, CR ASA 7 and OR Kencana. Observation parameters included plant height, number of leaves, number of productive branches, number of flowers, number of fruits per harvest period, total number of fruits, fruit set, fresh fruit weight per harvest period and total fresh fruit weight. The combination treatment of P3V3 produced the highest total number of fruits (102,33 fruits) and the heaviest total fresh fruit weight (288.10 g), significantly different from all treatments. The treatment of shoot trimming time significantly affected all observation parameters. The use of three varieties significantly affected the parameters of plant height, number of flowers, number of fruit plants per harvest and weight of fresh fruit plants per harvest